Blood Pressure and Heart Rate Variability in Primary Open-Angle Glaucoma and Normal Tension Glaucoma. (2nd December 2018) - Lindemann, Friederike; Kuerten, David; Koch, Eva; Fuest, Matthias; Fischer, Claudia; Voss, Andreas; Plange, Niklas
ABSTRACT: Purpose : Vascular dysfunction and ischemia are believed to play an important part in the pathogenesis of glaucoma and especially of normal tension glaucoma (NTG). The aim of the present study was to analyze the blood pressure (BP) and heart rate variability patterns in patients with primary open-angle glaucoma (POAG) and NTG compared with controls. Methods : In total, 37 patients with POAG, 27 patients with NTG, and 82 control subjects were included in a prospective clinical validation study. Continuous BP and heart rate were simultaneously recorded over 30 min (Glaucoscreen, aviant GmbH, Jena, Germany) under resting conditions. Time series of heart rate, systolic blood pressure (SBP) and diastolic blood pressure (DBP) were extracted and analyzed calculating univariate linear (time domain, frequency domain), nonlinear (symbolic dynamics), and bivariate (joint symbolic dynamics) indices. Results : Overall, 12 parameters could be identified that were significantly different when comparing POAG patients and controls, whereas 80 parameters were significantly different in NTG patients compared with controls. The optimum set consisting of three indices showed a sensitivity of 81.5% at a specificity of 86.6% for NTG patients compared with a sensitivity of 62.2% at a specificity of 82.9% for POAG patients. Conclusions : Alterations in BP variability and coupling with heart rate suggest impaired patterns of autonomic cardiovascular regulation in glaucoma patients especially in patients with NTG.